Carcinoid Tumors: An Ignored Cause of Appendicitis - Iqbal Memon; Komal Moorpani; Shafiq- (ziauddin University, 2024)
Background: Many conditions related to appendix present as appendicitis. These conditions can range from fecolith obstruction to tumors .Carcinoid tumors are most common tumors to present in appendix. Most of the carcinoid tumors in appendix present as appendicitis. Majority of the cases are diagnosed after histopathological examination, with 90% of the tumors measuring smaller than 1 cm with excellent prognosis after appendectomies. Tumors with the size of 2cm are treated with right hemicolectomy. Objective: To determine the frequency of carcinoid tumors in appendectomies using histopathological data. Methods: This was a retrospective study conducted at Ziauddin University Hospital, Nazimabad for a time period of 7 years from March 2005 to December 2012. 2,157 appendectomies were analyzed, out of which 13 appendectomy specimens were diagnosed as carcinoid tumors. Incidental and negative appendectomies were excluded from this study. Results: 0.60% of the appendectomy specimens were diagnosed as carcinoid tumors (n=13), male to female ratio was (5.5:1), 77% (n=10) of the tumors were up to 1 cm in size and 23% (n=3) of the tumors were of 1.5 cm in size. Majority of the tumors (n=9) had well differentiated cell types. 77% of the tumors were localized to the tip of the appendix, 15% of the tumors spread locally to the distal half of the appendix and 8% spread to the mesentery. Conclusion: Carcinoid tumors of the appendix, mostly present as appendicitis in early stage. While 90% of the cases show excellent prognosis with appendectomy, 10% of the cases might need further management. Key Words: Carcinoid Tumors, Appendix, Appendicitis, Appendectomy, Right Hemicolectomy.